Disassembly of myofibrils and potential imbalanced forces on Z‐discs in cultured adult cardiomyocytes. Issue 5 (28th April 2016) - Liu, Honghai; Qin, Wan; Wang, Zhonghai; Shao, Yonghong; Wang, Jingcai; Borg, Thomas K.; Gao, Bruce Z.; Xu, Meifeng
Abstract : Myofibrils are the main protein structures that generate force in the beating heart. Myofibril disassembly is related to many physiological and pathological processes. This study investigated, in a cultured rat adult cardiomyocyte model, the effect of force imbalance on myofibril disassembly. The imbalance of forces that were exerted on Z‐discs was induced by the synergistic effect of broken intercalated discs and actin–myosin interaction. Cardiomyocytes with well‐preserved intercalated discs were isolated from adult rat ventricles. The ultrastructure of cardiomyocyte was observed using a customized two‐photon excitation fluorescence and second harmonic generation imaging system. The contraction of cardiomyocytes was recorded with a high‐speed CCD camera, and the movement of cellular components was analyzed using a contractile imaging assay technique. The cardiomyocyte dynamic remodeling process was recorded using a time‐lapse imaging system. The role of actin–myosin interaction in myofibril disassembly was investigated by incubating cardiomyocytes with blebbistatin (25 μM). Results demonstrated that the hierarchical disassembly process of myofibrils was initiated from cardiomyocyte free ends where intercalated discs had broken, during which the desmin network near the free cell ends was destroyed to release single myofibrils. Analysis of force (based on a schematic model of cardiomyocytes connected at intercalated discs) suggests that breaking of intercalated discs caused force imbalance on both sides of the Z‐discs adjacent to the cell ends due to actin–myosin interaction. The damaged intercalated discs and actin–myosin interaction induced force imbalance on both sides of the Z‐discs, which played an important role in the hierarchical disassembly of myofibrils. © 2016 Wiley Periodicals, Inc.